EVALUASI PROGRAM PEMBERDAYAAN PETANI MELALUI MODEL CIPP (CONTEXT, INPUT, PROCESS, DAN PRODUCT) - Yoga Aldi Saputra; Mochamad Chazienul Ulum; Achmad Sofiyudin (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2022)
This research aims to evaluate the empowerment program for coffee farmers through the CIPP model to find out how far the empowerment efforts are implemented and the benefits are felt, especially for coffee farmers in Muncar Village, Gemawang District, Temanggung Regency. This study uses a descriptive qualitative approach with the Creswell model of data analysis method. Evaluation of coffee farmer empowerment is carried out comprehensively from upstream to downstream, starting from the cultivation, post-harvest, and marketing processes. The results showed that the empowerment of coffee farmers in Muncar Village was carried out through the collaboration of stakeholders. Overall, the empowerment in Muncar Village for coffee farmers has improved the welfare of farmers so that there is an increase in the economic source of family income. Keywords: Farmer Empowerment; Program Evaluation; Muncar Village; CIPP Model